Contribution of stilbene-imine additives on the structural, ionic conductivity performance and theoretical evaluation on CMC-based biopolymer electrolytes - Rahamathullah, Rafizah; Khairul, Wan M.; Isa, M. I. N. (Elsevier Sci Ltd, 2024)
Indexed by Scopus